Microbial communities, processes and functions in acid mine drainage ecosystems. (April 2016) - Chen, Lin-xing; Huang, Li-nan; Méndez-García, Celia; Kuang, Jia-liang; Hua, Zheng-shuang; Liu, Jun; Shu, Wen-sheng
Graphical abstract: Highlights: AMD microbial community is studied as a model system for microbial ecology. The taxonomic and phylogenetic diversity of AMD microorganisms. Functional and metabolic networks of AMD microbial communities. Biotechnological applications in biomining and AMD bioremediation. Combined with other novel approaches in AMD future studies. Abstract : Acid mine drainage (AMD) is generated from the oxidative dissolution of metal sulfides when water and oxygen are available largely due to human mining activities. This process can be accelerated by indigenous microorganisms. In the last several decades, culture-dependent researches have uncovered and validated the roles of AMD microorganisms in metal sulfides oxidation and acid generation processes, and culture-independent studies have largely revealed the diversity and metabolic potentials and activities of AMD communities, leading towards a full understanding of the microbial diversity, functions and interactions in AMD ecosystems. This review describes the diversity of microorganisms and their functions in AMD ecosystems, and discusses their biotechnological applications in biomining and AMD bioremediation according to their capabilities.